The explicit Gospel - Chandler, Matt, 1974- (Crossway, 2012)
Even if you go to church, it doesn't mean that you are being exposed (or exposing others) to the gospel explicitly. Sure, most people talk about Jesus, and about being good and avoiding bad, but the gospel message simply isn't there--at least not in its specificity and its fullness. Inspired by the needs of both the overchurched and the unchurched, and bolstered by the common neglect of the explicit gospel within Christianity, popular pastor Matt Chandler writes this punchy treatise to remind us what is of first and utmost importance--the gospel.